2017
DOI: 10.3390/su9050811
|View full text |Cite
|
Sign up to set email alerts
|

Open Innovation in Value Chain for Sustainability of Firms

Abstract: This piece serves as the guest editorial of the Special Issue on the 'Open Innovation in Value Chain for Sustainability of Firms'. Firstly, this editorial piece asks whether it is possible for firms to sustain their performance forever. Then, it reviews the popular literature on the value chain. Afterwards, it develops a research framework for open innovation in the value chain, and proposes five ways of open innovation taking place within it. These include user open innovation, customer open innovation, commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…Open innovation creates an inverted U-curve performance with a high-level fluctuation complexity according to three major factors: knowledge intensity, open innovation strategy, and time span. In addition, if we bear in mind the competitors that firms have, the complexity of open innovation effects will dramatically increase [40].…”
Section: Discussionmentioning
confidence: 99%
“…Open innovation creates an inverted U-curve performance with a high-level fluctuation complexity according to three major factors: knowledge intensity, open innovation strategy, and time span. In addition, if we bear in mind the competitors that firms have, the complexity of open innovation effects will dramatically increase [40].…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting the importance of the open innovation paradigm, many previous studies have revealed that its adoption can enhance organizational openness, the extent of external linkages, and the depth and breadth of knowledge search [16,[48][49][50]. Moving beyond the entrepreneurial perspective, using open innovation to external knowledge is reflected generally in institutional contexts [51].…”
Section: Social Trust and Open Innovationmentioning
confidence: 99%
“…JinHyo Joseph Yun and Tan Yigitcanlar said, "Firms cannot survive forever, basically because businesses of firms are embedded in the market, and society, which are changing dynamically.". Further, through "open innovation-open connections between technology, the market, and open business models-we may be able to create new opportunities to link technology, market and society" [29]. Open innovation is a concept that is often viewed as an important factor for the growth of an organization [30].…”
Section: Open Innovation For Senior Beauty Servicesmentioning
confidence: 99%